A Comparative study linguistic and literary paradox in the poems of ‛Abd al-wahhāb al-Bayātī and Mohammad Reza šafi’i Kadkani - Hediyeh Ghasemifard; Naser Zare (ادبیات تطبیقی, 2020)
A Comparative Study of Linguistic and Literary Paradoxes in the Poems of Abd al-Wahhab Al-Bayati and Mohammad-Reza Shafiei Kadkani*   Hediyeh Ghasemifard 1 Dr.Naser Zare 2                                                                                         1. Introduction Paradox is a proposition that logically seems incompatible and absurd, but can be meaningful by interpreting. Almost all poets have occasionally used it (see Abrams, 2005:244), as Shafiei Kadkani states "paradox is an image the two sides of its combination contradict each other conceptually like monarchy of the poverty" (Shafiei Kadkani, 1992:54). He believes that paradoxical images can be found in all periods of Persian poetry (Ibid: 57). Undoubtedly, in different periods of Arabic poetry, examples can also be stated: أو أبعدَ بُعدَنا بُعدَ التَدانی / وقرّبَ قربَنا قُربَ البعد (Al-Mutanabbi, 1988, 2: 78) (does it close our distance like keeping out our nearness and being far and nearness like closeness of separation?). Among the poets who had a high frequency of this literary method in their poems are Abd al-Wahhab al-Bayati (1926-1999) and Mohammad-Reza Shafiei Kadkani (1939), who are considered as powerful poets in the field of modern poetry. These two poets began their poetry with a romantic approach and then after moving from social realism, reached the symbolization phase. Social - political concerns with words that express sadness, a reason for common thoughts the two poets.  Their acquaintance with each other is undeniable; contemporaneity and attendance at one of the international congresses of poetry provided the opportunity to know each other. On the other hand, Al-Bayati really interested in  Persian poetry and Shafiei Kadkani  is completely familiar with  classic and contemporary Arabic literature; attention to Khayyam, Attar, Sohrawardi, and Hafiz are manifestations of Al-Bayaty's attempt to Iranian culture and about Shafiei Kadkani relation to the Arabic literature there is abundant evidence that does not need to be cited; since by a brief looking at his research works, translations and poems, his mastery can be found, and here it is not possible to deal with it. However, this does not mean that these two poets were influenced by the method and stylistic characteristics of each other, so it is possible to examine their stylistic properties within the framework of American School of Comparative Literature. In this paper, using descriptive-analytic method, only those poetry evidence will be examined that is in common between two poets in terms of style or implication.   2.Methodology In this study, by criticizing and analyzing similar and contradictory prominent examples in the poetry of two poets, we can examine the implications or constructs based on the American School of Comparative Literature and descriptive analytical method of applying paradox in their poetry.   3.Discussion Since paradoxes lead to a new recognition of the artwork, so Al-Bayati and Shafiei Kadkani, by leaving familiar meanings and creation of concepts seemingly the opposite of the fact, tangible to us a  world of realities. Paradoxical expressions and compositions in their poems can be divided into two types: linguistic and literary, and analyzed their similarities and differences as the paradoxical limitations of language is the most difficult of the paradoxes in terms of arrangement and construction of words, but many paradoxes in the grammar part of these two poets can be found. The paradox in the poetry of these two poets is found in the composition and document. Paradoxical compounds are purposely used to influence rhetoric, by combining contradictory words and creating exquisite images (Fotouhi, 2015: 328). These compounds are sometimes concise of one or more sentences with a contradictory meaning that are expressed in the form of adjectives (adjective and noun) and (Annexation and Annexed) in the poetry of two poets. Using the elements of nature in these contradictory combinations is a striking resemblance to the poetry of these two poet and Annexed) in the poetry of two poets. Using the elements of nature in these contradictory combinations is a striking resemblance to the poetry of these two poets.                                                      Predicative paradox (predicative paradox (documentary   paradox)) is another type of linguistic paradox that arises in the proposition of predicate and subject and can be examined in the poetry of these two poets at the level of two sentences or in the same constructions. These two poets sometimes use paradox at the level of two sentences using coordination of "and" or "no". The coordination letter of "and" is the most commonly used subordinated conjunctions. When several structures are linked together with "and" and construct a new structure, its artistic device find an alignment grammatical value. For this reason, two poets connect the contradictory words with "and", and affect the semantic and interpretive structures of the poem, as the reader suspects that he is confronted with a subject that is inaccurate because he is received the feeling of parallelism from the subordinating conjunction of "and". These two poets express their meaning and intention of paradox in a coordinated structure with the help of adverb of manner that shows different states or through a proposition.                                                                                  Another way to construct a paradox in the poetry of these poets is using figures of speech such as simile, metaphor, allusion, and tard va axe, which is referred to as literary paradox. The purpose of simile is to prove a trait (an adjective) from vehicle to tenor. So the tenor is the purpose of the word and vehicle is an instrument to help the desired purpose. Whenever, in a paradoxical image, the expressive purpose of the metaphor is considered, the vehicle should be conceived in such a way as to be incompatible with a word in the poem, then by eliminating the vehicle, the paradox will be remov. (Vahidian Kamyar, 1997:  284).  In the metaphorical paradox, the vehicle must be such that it makes a paradox with the word in the poem and by removing the vehicle, the paradox will be disappeared. One of the most important elements of imagery techniques in the poetry of these two poets is recognition. By using the recognition, they strive to give life to all phenomena and objects. Therefore, to translate their feelings, they use implicit metaphor. In addition to applying the implicit metaphor, explicit metaphors are also found in the poems of two poets. Another paradoxical style in the poetry of these two poets is using irony. In this figure of speech, the vehicle (superficial words) is such that make contradictions with the words of the language, and then this contradiction is removed by eliminating the vehicle. Another literary style in applied paradoxes of the poets is using chiasmus and shatah, that is, the poet uses the combination of opposing words and then by subordinating conjunction of "and" and moving the arrangement of words, make a monotonic relation with the elementary composition. This artistic device in an impossible setting, and then movement of the words, and finally the coherence between them, first arouses an ambiguity that will be feasible by contemplation and discovering the main idea of the poet.   4.Conclusion A Part of Al-Bayati and Shafiei Kadkanie's insight is related to paradoxical images that in its structure, has poetic anxiety. Choosing vocabulary, deviation of norms, and paying attention to aesthetic aspects of the word are important features in the poetic contradictions of these two poets. The paradoxical application of their pomes can be analyzed on the basis linguistic and literary construction. Paradoxical expressions are observed both in the form of predicate and combination in their poems, with a higher frequency of predicate. In many of the paradoxical images of these two poets, it can be possible to observe clear imagery which shows a similarly emotional space, which is what led us to perform this literary study . One of these images is lightness-darkness and the other is the image of death and life in which they reflect hope. Two poets use the elements of nature in paradoxical terms for symbolic expression of concepts whose frequency is higher in Shafiei Kadkani's poetry due to his ruralistic spirit. If al-Bayati expresses his paradoxical poems in the form of death, homeland, prison and fire, Shafiei Kadkani reflects those ideas by the nature and subtle words. In some Shafiei Kadkani paradoxes, in particular, "the black light of devil", a kind of shatah can be seen that cannot be considered a place for this perspective in Al-Bayati's paradoxes. In the paradoxes of Al-Bayati due to socialist beliefs, sorrow and sadness can be felt more than Shafiei Kadkani, although the veins of hope are often obvious in the poetry of the two poets. These two poets do not try to hide the content for the reader, but it can be understood with a little contemplation and searching meaning in the ambiguity and layers of the word. Therefore, paradoxical images can be one of the reasons of acceptance of their poems. Keywords:Paradox, Comparative Literature, Contemporary Arabic and Persian Poetry, Abd al-Wahhab Al-Bayati, Shafiei Kadkani. References [In Persian]: -Abbasi, H. (2008), Rain’s Book of Travel. First Edition. Tehran: Sokhan. -Abrams, M. (2005).  A Glossary of literary Terms. Translated.  by: Saeed Sabzian. First  Edition. Tehran: Rahnama. -Al-Bayati, A . (1990). Collected Poems. Fourth edition. Beirut: Dar al- Aawda. -Alipour, M. (2008). Making and Writing of Today Poetry. First Edition. Tehran: Ferdows. -Al-Khayat, J. (1987). Modern Iraqi Poetry: Transition and Progress. Second Edition. Beirut: Dar al-Raed al-Arabi. -Al-Meqhdad, H. (2015). A New Movement in the Modern Iraqi Poetry. First Edition. Beirut: Dar al-Kutub al-Arabi. - Al-Mutanabbi, Ahmad. (1986). Description of Al-Mutanabbi’s  Divan. Abd -al Rahman al-Barquqi.  Volumes. I and II. Beirut: Dar al--Kitab al-Arabi. -Chenari, A. (1998). Paradox in Persian Poetry. First Edition. Tehran: Farzan -e-Rooz. -Fotouhi, M. (2016). Rhetoric of Image. Fourth Edition. Tehran: Sokhan. -Hassanli, K . (1385). The Sun's Eye. First Edition. Shiraz: Navid. -Rezqh, K. (1997). A Study of the Poetry of Abd al-Wahhab al-Bayati. First Edition. Beirut: Al- Ashraf. -Rumi, J. (1983 ). Collected Poems -e Shams-e Tabrizi. First Edition.  Edited by of‌‌  Badi Foruzanfar. Tehran: Amir Kabir -Saadi, M. (1993). Complete Work of Saadi. Edited by Mohammad Ali Foroughi. By the Efforts of Baha al-din Khorramshahi. Ninth Edition. -Shafiei Kadkani, M (2009). Th Secon Millennium of Mountain Gazelle. Fifth Edition. Tehran: Sokhan. -Shafiei Kadkani, M. (1371). The Poet of Mirrors (A Review of the Indian Style  and Bidel’s Poetry). Third Edition. Tehran: Agah. -Shafiei Kadkani, M. (1998). A Mirror for Sounds. Second Edition. Tehran: Sokhan. -Shafiei Kadkani, M. (2013). The language of Poetry in Sofia Prose. First Edition. Tehran: Sokhan. -Sharifi, F. (2014). The Poem of Our Time (Mohammad Reza Shafiei Kadkani). First Edition.Tehran: Negah. -Tahbaz, S. (2001). The Unmatched Fighting Cock (Life and Art of Houshang Irani). First Edition. Tehran: Farzan Rooz. -Tehran: Amir Kabir. *Date received: 04/06/2019                                Date accepted: 25/11/2019 1 Ph.D. Candidate of Arabic Language and Literature, Faculty of Literature and Humanities, University of  Persian Gulf  University, Bushehr, Iran, Email: hdghasemifard@gmail.com 2. Faculty Member of Arabic Language and Literature, Persian Gulf University, Bushehr, Iran Email: nzare@pgu.ac.ir (Corresponding author)